Pengembangan Lembar Kegiatan Siswa Berbasis Etnosains yang Berkarakter pada Materi Taksonomi Tumbuhan untuk Siswa SMA: The Development Student Worksheet Based on Etnoscience Characterized on Plant Taxonomic Materials at Senior High School - Wenny Nureflia; Revis Asra; Nazaruddin Nazaruddin (Universitas Jambi, 2018)
Traditional knowledge held by society contains character values ​​and scientific concepts, but such knowledge is frequently ignored. This study aims to develop Student Activity Sheets on plant taxonomy based on ethnoscience for high school, and analyze the response of teachers and students to the products developed. The model used in this study follows the ADDIE stages. The instrument used is a response questionnaire given to teachers and students. Product feasibility was analyzed through the results of material expert validation and design experts. The result of the study is in the form of student worksheet based on ethnoscience and character values ​​for plant taxonomy material. The results of product validation obtained a score of 74 (